Pendekatan Pragmatik dalam Analisis Cerpen “Robohnya Surau Kami” Karya A.A. Navis - Khaila Riyanni; Liya Adqiyah; Nadia Mayasari; Ahmad Supena (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This article analyzes the short story “Robohnya Surau Kami” by A.A. Navis using the pragmatic literary criticism approach technique. This research is based on the knowledge that literary works function as a means of communication that provides moral, educational, and social messages to readers in addition to being a means of creative expression. The pragmatic approach examines the extent to which short stories can offer educational benefits and values by focusing on the role of the reader in receiving and evaluating literary works. By analyzing the basic components of short stories and their application in the social context of society, this study uses an analytical descriptive method. The findings of this study are expected to help readers to understand the role of pragmatics in literary criticism and advance the study of Indonesian literature, especially in recognizing literary works as windows to social reality and teaching tools for moral principles. Moreover, by emphasizing the importance of balance between ritual worship and social responsibility, the analysis shows that this short story offers a sharp moral critique, especially in the religious and social realms. Therefore, the work serves as entertainment and a relevant social mirror to teach readers life lessons and improve their quality.